Medial Education as a Means to Medial Literacy of School Youth - Cingelová, Gabriela (Civilia, 2015)
The text deals with media education in primary and secondary schools. It presents its contents, objectives and tasks. Finally, it provides an example of the practice of teacher education - developing ZTV literacy film.
Keywords: Media; Media Education; School; Children; Crosscutting theme; Didactics; Film; Literacy